The Levels of Heavy Metals in Semi-Processed Food Products and Their Impact on Human Health - Bakhtiyorovna, Avliyakulova Musharraf; Sirojidin qizi, Kamolova Rakhima (American Journal of Bioscience and Clinical Integrity, 2026)
The levels of lead and cadmium in semi-finished food products were analyzed and compared with sanitary standards. The results showed that the presence of heavy metals largely depends on environmental conditions, production processes, and the quality of raw materials, while exceeding permissible limits can negatively affect human health. The study highlights the need to ensure food safety and strengthen control measures.